Acute inhibition of hunger-sensing AgRP neurons promotes context-specific learning in mice - Felicia Reed; Alex Reichenbach; Harry Dempsey; Rachel E. Clarke; Mathieu Mequinion; Romana Stark; Sasha Rawlinson; Claire J. Foldi; Sarah H. Lockie; Zane B. Andrews (Elsevier, 2023)
Objective: An environmental context, which reliably predicts food availability, can increase the appetitive food drive within the same environment context. However, hunger is required for the development of such a context-induced feeding (CIF) response, suggesting the neural circuits sensitive to hunger link an internal energy state with a particular environment context. Since Agouti related peptide (AgRP) neurons are activated by energy deficit, we hypothesised that AgRP neurons are both necessary and sufficient to drive CIF. Methods: To examine the role of AgRP neurons in the CIF process, we used fibre photometry with GCaMP7f, chemogenetic activation of AgRP neurons, as well as optogenetic control of AgRP neurons to facilitate acute temporal control not permitted with chemogenetics. Results: A CIF response at test was only observed when mice were fasted during context training and AgRP population activity at test showed an attenuated inhibitory response to food, suggesting increased food-seeking and/or decreased satiety signalling drives the increased feeding response at test. Intriguingly, chemogenetic activation of AgRP neurons during context training did not increase CIF, suggesting precise temporal firing properties may be required. Indeed, termination of AgRP neuronal photostimulation during context training (ON-OFF in context), in the presence or absence of food, increased CIF. Moreover, photoinhibition of AgRP neurons during context training in fasted mice was sufficient to drive a subsequent CIF in the absence of food. Conclusions: Our results suggest that AgRP neurons regulate the acquisition of CIF when the acute inhibition of AgRP activity is temporally matched to context exposure. These results establish acute AgRP inhibition as a salient neural event underscoring the effect of hunger on associative learning.